The teacher of nomad land : a World War II story - Nayeri, Daniel (Levine Querido, 2025)
"1941. The German armies are storming across Europe. Iran is a neutral country occupied by British forces on one side. Soviet forces on another. Soldiers fill the teahouses of Isfahan. Nazi spies roam the alleyways. Babak and his little sister have just lost their father. Now orphans, fearing they will be separated, the two devise a plan. Babak will take up his father's old job as a teacher to the nomads. With a chalkboard strapped to Babak's back, and a satchel full of textbooks, the siblings set off to find the nomad tribes as they make their yearly trek across the mountains. On the treacherous journey, they meet a Jewish boy, hiding from a Nazi spy. And suddenly they are all in a race for survival. Against the backdrop of World War II comes an epic adventure in faraway places. Through the cacophony of soldiers, tanks, and planes, can young hearts of different creeds and nations learn to find a common language?"--